ANALISIS PEMASARAN KOPRADI DESA TAMBU KECAMATAN BALAESANG KABUPATEN DONGGALA - Minhar, Iksan; Lamusa, Arifuddin; Sulaeman, Sulaeman (AGROTEKBIS, 2016)
This study aims to determine the copra marketing channels, the amount of margin on each marketing channel, and the price part that received by farmers in each marketing channel and the copra marketing efficiency of each marketing channel. The study was conducted from March to May 2015 at Tambu Balaesang District of Donggala. Respondents were farmers, traders and retailers as consumers. Sampling of respondents performed by using simple random sampling and selected 34 respondents from total 130 farmers in this village. Sampling for merchant respondentâs was by tracing method and got 3 collectors and 1 retailer respondents. The total number of respondents was 38. The analysis was used the farmers share. The analysis showed that the copra marketing margin obtained for the first channel was 500 per kg. The part of this price that received by farmers in this first channel was 90,60%, and the second channel is 94,44%. Thus, the greatest part of the price received by farmers is on the second channel of marketting. Copra marketing channels in Tambu village consists of two channels, namely: 1) Farmers âmiddle manâConsumers, 2) Farmers âConsumers.In the first channel, efficiency value that received by farmers was 9,40% and 5.56% at second channel of marketing, respectively. Thus the direct channel from farmers to consumers is more efficient.Key Words: Copra, farmershare, marketing analysis.